Role of Perfusion Parameters on Outcomes and Safety of Endovascular Therapy in Posterior Cerebral Artery Stroke - Norma J. Diel; Davide Strambo; Mohamad Abdalkader; Muhammad M. Qureshi; Vincent Dunet; Bruno Bartolini; Silvia Pistocchi; Daniel Strbian; Silja Räty; Christian Herweh; Markus Möhlenbruch; Marta Olivé-Gadea; et al. (Stroke, 2026)
BACKGROUND: The optimal management of isolated posterior cerebral artery occlusion (iPCAO) remains unclear. We investigated whether baseline perfusion imaging parameters are associated with clinical outcomes and whether they modify the association between endovascular therapy (EVT) and outcomes in iPCAO. METHODS: This prespecified secondary analysis of the international, multicenter, observational PLATO (Posterior Cerebral Artery Occlusion) registry (35 centers, 10 countries, 2015–2025) included consecutive adults with unilateral iPCAO and baseline perfusion imaging (computed tomography or magnetic resonance imaging) with reconstructed parameters. The primary end point was an excellent 90-day outcome (modified Rankin Scale score, 0–1). Perfusion parameters included hypoperfusion volume, infarct core volume, and mismatch ratio. The primary analysis used multivariable mixed-effects regression models (center as random effect) to assess associations between perfusion parameters and outcomes, adjusting for age, sex, treatment year, prestroke modified Rankin Scale score, baseline National Institutes of Health Stroke Scale score, diabetes, stroke cause, posterior circulation Acute Stroke Prognosis Early Computed Tomography Score, occlusion site, intravenous thrombolysis, and onset-to-door time. To test whether the association between EVT and outcomes varies according to baseline perfusion parameters, we evaluated treatment-by-perfusion interactions by including interaction terms (treatment×perfusion parameter) in inverse probability of treatment weighting–adjusted models, with results expressed as ratios of odds ratios (ORs). RESULTS: Of 1811 patients with iPCAO, 443 met inclusion criteria (median age, 74 years; 41.8% female). Larger hypoperfusion volume was associated with lower odds of excellent outcome (adjusted OR, 0.72 [95% CI, 0.58–0.89] per 1-unit increase in natural logarithm–transformed volume). No interaction between perfusion parameters and EVT was observed for the primary outcome. However, increasing core volume was associated with a progressively less favorable modified Rankin Scale score shift (ratio of OR, 0.66 [95% CI, 0.48–0.90]; P interaction =0.009) and higher mortality (ratio of OR, 1.82 [95% CI, 1.10–3.03]; P interaction =0.021) with EVT compared with medical management. Increasing hypoperfusion volume was associated with a higher risk of symptomatic intracranial hemorrhage with EVT (ratio of OR, 10.15 [95% CI, 1.06–96.93]; P interaction =0.044). CONCLUSIONS: In iPCAO, perfusion imaging provides independent prognostic information but does not identify patients with potential benefit from EVT and may instead indicate those at higher procedural risk. REGISTRATION: URL: https://osf.io/62mwt ; Unique identifier: NCT05291637.